Analisis Karakteristik Moda Transportasi Umum Mobil Pete-Pete dan Ojek di Pasar Sentral Sudu - Muhammad Ilham Nanda; Rahmawati; Misbahuddin (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study will analyze the factors that influence the choice of public transportation modes in Sudu Central Market. The study will focus on two types of transportation modes: pete-pete cars and motorcycle taxis. We used the binomial logistic regression method to identify the variables that influence user decisions in choosing between the two modes of transportation. The study surveyed 100 respondents, testing variables such as cost, travel time, comfort, safety, frequency, and accessibility. The results are clear: comfort, travel time, safety, and accessibility have a significant influence on the choice of transportation modes, with a p value <0.05. The results are clear: the more comfortable, faster, safer, and more accessible the transportation mode, the greater the chance of users choosing a pete-pete car. Conversely, costs had a negative effect, where higher costs meant less likelihood of choosing a pete-pete car. The frequency of departure had no significant impact in this regression model.